Dinamização dos mercados de trabalho municipais e a desigualdade de rendimentos no Brasil - Letícia Gavioli (2016)
This work provides an investigation of the evolution of wage inequality considering the dynamism of labor markets in Brazilian municipalities. Current literature provides the means of specifying supply and demand factors for labor. Those factors present potential economic dynamism for the purposes of this research, being characteristics that foster changes in the labor market impacting the distribution of wages and calls into question unexplored dimensions of wage inequality in Brazilian municipalities. In other words, the dynamics and composition of industry sectors and labor occupation at the municipal level over time and its relation to wage inequality. To analyze these trends, we established three categories of dynamic municipalities, including dynamic, stable and non-dynamic municipalities. Those take into account industry sectors and labor occupations that allows dynamization, e.g. related to technology, complex tasks and the employment of workers with high education levels. Using RAIS microdata for 2003 and 2013, we were able to observe that the sectors of modern industry and productive services and the occupational group of arts and sciences professionals are the ones most sensitive for the referred modernizing changes. Therefore, our typology is based on those three groups. Our results show using the quantile regression method - the difference in the evolution of the structure of individual inequality when comparing municipalities which are not dynamic to those which are. In general, the increase of salaries of dynamic municipalities in any of the typologies, was relatively higher than those which have not experienced the process of dynamization. The result of this study shows that wages for workers living in dynamic municipalities, due to their rapid growth, can approximate their salaries to individuals that live in stable municipalities. Comparisons between the typologies, with respect to education level, suggest that the typology of dynamic municipalities with modern industry were the most favorable to the relative growth of wage on the basis of distribution. This is true both in relation to other municipalities in the same typology, and in relation to dynamic municipalities of the other typologies. Regarding college degree attainment, the dynamics of that typology also tends to be relatively more favorable to the top of the earning distribution. Considering high school degree attainment, the top of the distribution was relatively more favored in the dynamic municipalities of the professionals typology, as well as the median with respect to college. On the other hand, the dynamic municipalities of the productive services typology proved relatively more advantageous for high school degree workers in the median, which did not prevent an increase in the gap between the earnings of the top and the bottom of the distribution (bipolarization), both in relation to the high school degree workers and college degree earners.